Gambaran Pelaksanaan Kegiatan Pembelajaran untuk Meningkatkan Kemampuan Literasi Matematika Siswa - Rahma Muti’ah; Irmayanti Irmayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
One indicator that can be used as a success in the educational process is the value of students' mathematical literacy abilities. In Satu Atap Aek Natas Junior Secondary School out of 122 samples, the results of 87 students are still relatively low. Mathematical literacy is influenced by, among others, the interest in reading mathematics and low family social support. For this reason, the solution offered in the implementation of community service is to carry out learning activities using a recitation-assisted PMR approach, the application of the principle of economic tokens accompanied by the use of a contact book. Participants in the implementation of this service consisted of 30 students, 30 parents/guardians of students, and 15 teachers. Based on the results of the implementation of community service there is an increase in the average value of literacy skills, interest in reading and social support of the family before the implementation and after the implementation of service.